Inertia and primary frequency modulation strategy for a doubly fed induction generator based on supercapacitor energy storage control. Issue 9 (15th July 2022) - Cui, Sen; Yan, Xiangwu; Siddique, Abubakar
ABSTRACT: Doubly fed wind turbines cannot respond to changes in grid frequency under maximum power point tracking control. The traditional deloading frequency control suffers from problems, such as low power generation efficiency, small speed adjustment range, and frequent starting of pitch angle control. An inertia and primary frequency modulation (FM) strategy for a doubly fed wind turbine based on supercapacitor energy storage control is proposed in this study. Virtual inertia and primary frequency adjustments are realized by supercapacitor control. Changing or increasing the additional control of the wind turbine is unnecessary. The proposed strategy can improve the disturbance resistance and self-stabilization of a single wind turbine. The capacity of the energy storage unit is optimally configured in accordance with the cost and charging/discharging efficiency of the actual supercapacitor module. Comparing and evaluating the economics of the primary FM scheme of an active power reserve provide a powerful economic advantage. Simulations and experiments show that inertial support, primary frequency adjustment capability, and power generation benefits are significantly improved compared with those in the conventional primary frequency control. This study provides new ideas for the modified inertia and primary FM function of a doubly fed wind turbine.